Neuroprotective Effects of Phytochemicals against Aluminum Chloride-Induced Alzheimer's Disease through ApoE4/LRP1, Wnt3/β-Catenin/GSK3β, and TLR4/NLRP3 Pathways with Physical and Mental Activities in a Rat Model - Ahmed Mohsen Elsaid Hamdan; Fatimah Hussain J. Alharthi; Ahmed Hadi Alanazi; Soad Z. El-Emam; Sameh S. Zaghlool; Kamel Metwally; Sana Abdulaziz Albalawi; Yahia S. Abdu; Reda El-Sayed Mansour; Hoda A. Salem; Zakaria Y. Abd Elmageed; Karema Abu-Elfotuh (MDPI AG, 2022)
Background: Alzheimer's disease (AD) is a neurodegenerative disorder that is associated with abnormal cognition. AD is aided in its initiation and progression by hereditary and environmental factors. Aluminum (Al) is a neurotoxic agent that causes oxidative stress, which is linked to AD progression. Additionally, Nrf2/HO-1, APOE4/LRP1, Wnt3/β-catenin, and TLR4/NLRP3 are the main signaling pathways involved in AD pathogenesis. Several phytochemicals are promising options in delaying AD evolution. Objectives: This study aimed at studying the neuroprotective effects of some phytochemicals as morin (MOR), thymol (TML), and thymoquinone (TMQ) on physical and mental activities (PhM) in Al chloride (AlCl3)-induced AD rat model. Another objective was to determine the specificity of phytochemicals to AD signaling pathways using molecular docking. Methods: Eighty male Dawley rats were divided into eight groups. Each group received: saline (control group), AlCl3, (ALAD), PhM, either alone or with a combination of MOR, TML, and/or TMQ for five weeks. Animals were then subjected to behavioral evaluation. Brain tissues were used for histopathological and biochemical analyses to determine the extent of neurodegeneration. The effect of phytochemicals on AlCl3-induced oxidative stress and the main signaling pathways involved in AD progression were also investigated. Results: AlCl3 caused a decline in spatial learning and memory, as well as histopathological changes in the brains of rats. Phytochemicals combined with PhM restored antioxidant activities, increased HO-1 and Nrf2 levels, blocked inflammasome activation, apoptosis, TLR4 expression, amyloide-β generation, and tau hyperphophorylation. They also brought ApoE4 and LRP1 levels back to normal and regulated Wnt3/β-catenin/GSK3β signaling pathway. Conclusions: The use of phytochemicals with PhM is a promising strategy for reducing AD by modulating Nrf2/HO-1, TLR4/NLRP3, APOE4/LRP1, and Wnt3/β-catenin/GSK-3β signaling pathways.